Improving adhesion between luting cement and zirconia-based ceramic with an alternative surface treatment - Aurealice Rosa Maria MARTINS; Valéria Bisinoto GOTTI; Marcos Massao SHIMANO; Gilberto Antônio BORGES; Luciano de Souza GONÇALVES (Sociedade Brasileira de Pesquisa Odontológica, 2015)
This study evaluated the influence of an alternative surface treatment on the microshear bond strength (μsbs) of zirconia-based ceramic. Thirty-five zirconia disks were assigned to five groups according to the following treatments: Control (CO), glass and silane were not applied to the zirconia surface; G1, air blasted with 100μm glass beads + glaze + silane; G2, a gel containing 15% (by weight) glass beads applied to the ceramic surface + glaze + silane; G3, a gel containing 25% (by weight) glass beads applied to the ceramic surface + glaze + silane; and G4, a gel containing 50% (by weight) glass beads applied to the ceramic surface + glaze + silane. The specimens were built up using RelyX ARC®, according to the manufacturer's recommendations, and inserted in an elastomeric mold with an inner diameter of 0.8 mm. The μsbs test was performed using a testing machine at a crosshead speed of 0.5 mm/min. ANOVA and Tukey's test (p < 0.05) were applied to the bond strength values (in MPa). CO (15.6 ± 4.1) showed the lowest μsbs value. There were no statistical differences between the G1 (24.9 ± 7.4), G2 (24.9 ± 2.3), G3 (35.0 ± 10.3) and G4 (35.3 ± 6.0) experimental groups. Those groups submitted to surface treatments with higher concentrations of glass showed a lower frequency of adhesive failures. In conclusion, the glass application improved the interaction between the ceramic and the luting cement.